Інтертекстуальність українського інтернет-дискусу пореволюційного періоду - Левченко, Олена (Видавництво Львівської політехніки, 2015)
The article focuses on the study of intertextemes and their markers in the Ukrainian Internet discourse. The research is conducted on the material of intertexemes followed by markers of intertextuality which have been extracted from the texts published in the Ukrainian segment of the Internet within the period of 2014 – beginning of 2015. Factual research base comprises about 1,800 units. The conclusions concerning the peculiarities of intertextuality markers in the modern Ukrainian Internet discourse, qualitative composition of intertextemes and dominant cultural impact have been made.
Keywords: інтертекстуальність; інтертекстема; інтернет-дискурс; маркер інтертекстуальності